2010
DOI: 10.1111/j.1749-6632.2010.05626.x
|View full text |Cite
|
Sign up to set email alerts
|

Advantages and considerations in the confirmation of mitochondrial DNA mutations by denaturing HPLC and pyrosequencing

Abstract: Human mitochondrial DNA (mtDNA) encodes 13 polypeptides essential for oxidative phosphorylation. Because of the unique features of "replicative segregation" and "threshold expression" of mtDNA genetics, identification of homoplasmy versus heteroplasmy status is critical. Results from various detection methods may lead to different interpretations on formation or outcome of mtDNA mutations, such as the conclusion of somatic mutation versus genetic drift in cancers. Denaturing high-performance liquid chromatogra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2014
2014
2016
2016

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 41 publications
1
3
0
Order By: Relevance
“…By conducting analysis on a serial of samples with different percentages of mutant, Janne et al reported that the sensitivity of SN/WAVE-HS method for the EFRF gene reached 1% of mutant [10], which was similar to 2% observed in this study for plasmids with an SNP. We identified that DHPLC was suitable to detect mutant at 5% or greater in this study, which was consistent with that reported in our previous study [4] and in other studies [8], [27] for mtDNA. Because testing on the optimal temperatures required for DHPLC analysis is not conducted for SN/WAVE-HS analysis, and the WAVE HS System is superior to gel electrophoresis for the identification of cleaved DNA fragments with their approximate sizes, theoretically, the SN/WAVE-HS platform should provide a considerably more efficient and convenient method than DHPLC for the screening of mtDNA mutations and heteroplasmy.…”
Section: Discussionsupporting
confidence: 93%
See 3 more Smart Citations
“…By conducting analysis on a serial of samples with different percentages of mutant, Janne et al reported that the sensitivity of SN/WAVE-HS method for the EFRF gene reached 1% of mutant [10], which was similar to 2% observed in this study for plasmids with an SNP. We identified that DHPLC was suitable to detect mutant at 5% or greater in this study, which was consistent with that reported in our previous study [4] and in other studies [8], [27] for mtDNA. Because testing on the optimal temperatures required for DHPLC analysis is not conducted for SN/WAVE-HS analysis, and the WAVE HS System is superior to gel electrophoresis for the identification of cleaved DNA fragments with their approximate sizes, theoretically, the SN/WAVE-HS platform should provide a considerably more efficient and convenient method than DHPLC for the screening of mtDNA mutations and heteroplasmy.…”
Section: Discussionsupporting
confidence: 93%
“…The mtDNA-specific primers that did not amplify DNA from 143B-ρ 0 cells for the amplicon of nt 3374–3894 have been previously described [4]. The forward primer 5′-GAAACTTAGATCCAGGTGTCGC-3′ and reverse primers 5′-AGCAGCAATTTGTAAGTGTCCC-3′ were designed as nDNA-specific primers, which amplified a fragment of human SOD2 gene across an exon and an intron with the length of 293 bp.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations